The Equilibrium Size and Value-Added of Venture Capital - Francesco Sannino (The Journal of Finance, 2024)
I model positive sorting of entrepreneurs across the high and low value-added segments of the venture capital market. Aiming to attract high-quality entrepreneurs, inefficiently many venture capitalists (VCs) commit to provide high value-added by forming small portfolios. This draws the marginal entrepreneur away from the low value-added segment, reducing match quality in the high value-added segment too. There is underinvestment. Multiple equilibria may emerge, and they differ in aggregate investment. The model rationalizes evidence on VC returns and value-added along fundraising “waves” and when the cost of entrepreneurship falls, and generates untested predictions on the size and value-added of venture capital.
Keywords: 330